NON-BLOOD ANEMIA DETECTION: A SYSTEMATIC REVIEW - Tasya Nurlaila Dilla; Melyana Nurul Widyawati; Yeyen Wulandari Dhanio; Desiska Pricilia; Rili Ronia Nggusual; Nur Syahria; Maya Latifatul Masruroh (Journal of Applied Health Management and Technology, 2021)
Background: Anemia is a serious global health problem that may result in hemorrhage, premature birth, Low Birth Weight, and fetal development disorder. To this day, detection for anemia in midwifery care is still invasive, despite the fact that it has some drawbacks, including the need for blood sampling, expensive cost, the need for skillful health care personnel, and the need for laboratory facility. All these drawbacks make people less interested in undergoing examination. The WHO recommends hemoglobin (Hb) screening using non-invasive methods. Method: This systematic review is based on the PRISMA protocol with searches from the database of Google Scholar, Pubmed, and Science Direct for publications published from 2010 to 2019. The keywords used were: “Early Detection for Anemia”, “Screening for Anemia”, and “Non-Invasive Anemia Detection” with inclusion criteria of publications written in English and Bahasa Indonesia, and those published between 2011 and 2019, which resulted in 16 selected publications.Results: Searches for publications landed 302 published publications, 16 of which meet the criteria. These 16 selected publications consist of 10 publications detecting anemia using fingers, and the remaining six, detect anemia using conjunctiva.  Conclusion: Non-invasive methods are deemed effective in detecting anemia because they are easy to implement, do not require blood sampling, affordable, and do not need skillful health care personnel to administer them, as well as having less possibility for infection. These advantages make non-invasive methods applicable in midwifery care.